2022
DOI: 10.3389/fmicb.2022.845144
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Screening for Marine Prokaryotes and Eukaryotes With Selective Preference for Polyethylene and Polyethylene Terephthalate Surfaces

Abstract: Marine plastic debris serve as substrates for the colonization of a variety of prokaryote and eukaryote organisms. Of particular interest are the microorganisms that have adapted to thrive on plastic as they may contain genes, enzymes or pathways involved in the adhesion or metabolism of plastics. We implemented DNA metabarcoding with nanopore MinION sequencing to compare the 1-month-old biomes of hydrolyzable (polyethylene terephthalate) and non-hydrolyzable (polyethylene) plastics surfaces vs. those of glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
(110 reference statements)
0
10
0
Order By: Relevance
“…This notion was validated in a recent study that showed that the polymer type affects microbiome composition and metabolic functionality in early marine plastic communities but not mature communities [26]. Using linear regression analysis, we recently identified prokaryotic and eukaryotic taxa that were significantly enriched on specific plastic polymers in the marine environment [20]. However, in agreement with the previous studies mentioned above, we showed here that greater variability is expected during even earlier developmental stages of the plastic communities, as the different polymer samples were most dissimilar in the 2-day time point, followed by a gradual, consistent shift toward equilibrium.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…This notion was validated in a recent study that showed that the polymer type affects microbiome composition and metabolic functionality in early marine plastic communities but not mature communities [26]. Using linear regression analysis, we recently identified prokaryotic and eukaryotic taxa that were significantly enriched on specific plastic polymers in the marine environment [20]. However, in agreement with the previous studies mentioned above, we showed here that greater variability is expected during even earlier developmental stages of the plastic communities, as the different polymer samples were most dissimilar in the 2-day time point, followed by a gradual, consistent shift toward equilibrium.…”
Section: Discussionmentioning
confidence: 56%
“…The microbial communities of the plastisphere are affected by different factors, including geography and season [4-7], immersion/incubation time [8, 9], salinity [10] and plastic weathering state [11, 12]. While the composition of the plastic-attached microbiome differs from that of natural organic debris [13], the effect of the plastic polymer type remains elusive and often undetectable [8, 14-16]. A few studies showed polymer-based variations in the early marine plastic microbiome, a few days to several weeks old [17-22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the latter, it is noteworthy to mention the genus Alcanivorax that showed high abundance in all of the Yarkon repeats and was also identified in lower abundance in Sado summer samples, suggesting that this genus is favorable of higher temperatures. In two separated incubation experiments, we previously identified substantial Alcanivorax presence in association with PE surfaces (Davidov et al, 2020;Marsay et al, 2022). Alcanivorax species are well-known degraders of alkanes and petroleum (Hara et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…The plastic polymer type is not considered a major factor that is affecting the plastisphere microbiome in the natural environment (Oberbeckmann et al, 2018;Laverty et al, 2020). However, short-term incubation studies have shown that some bacteria have a significant preference toward specific plastic polymers (Marsay et al, 2022).…”
Section: Discussionmentioning
confidence: 99%